Pelaksanaan Pemungutan Pajak Hotel di Padangsidimpuan Perspektif Fiqh Siayasah - Batubara, Rahmat (Jurnal El-Thawalib, 2022)
This study examines the implementation of hotel taxes based on Law Number 04 of 2013 Article 8 concerning the Use of Local Taxes in Padansidimpuan. Taxes are people's contributions to the government and the money is used to build public facilities and help others. This type of research is in the form of field research or field research with a qualitative approach. Primary data sources come from employees of the Revenue Service and employees of the Padangsidimpuan City Hotel, while secondary data comes from related journal articles and books. Data collection techniques with interviews and documentation while data analysis techniques using descriptive qualitative. The results of this study are the implementation of regional regulations of the city of Padangsidimpuan no. 04 of 2013 article 08 regarding regional taxes in the city of Padangsidimpuan are as follows; The implementation of Hotel Tax Collection Based on Regional Regulation of Padangsidimpuan City No. 04 of 2013 Article 08 concerning Padangsidimpuan Regional Tax has not run optimally. This can be seen from the 6 hotels that were the subject of this study. There are two hotels that are late in making tax payments. Then, several obstacles to implementing hotel tax collection in Padangsidimpuan City, namely the lack of awareness of taxpayers about their responsibilities in paying taxes, sanctions that are not working properly. In addition, revenue service officers also do not socialize to taxpayers. A tax payment system that is too complicated makes it difficult for taxpayers to manage files related to taxpayer deposits. Third, regarding the review of siyasa fiqh, the scholars also recommend that tax collection in Indonesia must pay attention to rules such as Islamic law. Indonesia has not yet based its state ideology on Islamic law. Thus, it is necessary to have a thorough study to provide an explanation regarding the payment of taxes for Muslim communities in terms of siyasa fiqh.